Setup for microwave stimulation of a turbulent low-swirl flame. (7th April 2016) - Ehn, Andreas; Hurtig, Tomas; Petersson, Per; Zhu, Jiajian; Larsson, Anders; Fureby, Christer; Larfeldt, Jenny; Li, Zhongshan; Aldén, Marcus
Abstract: An experimental setup for microwave stimulation of a turbulent flame is presented. A low-swirl flame is being exposed to continuous microwave irradiation inside an aluminum cavity. The cavity is designed with inlets for laser beams and a viewport for optical access. The aluminum cavity is operated as a resonator where the microwave mode pattern is matched to the position of the flame. Two metal meshes are working as endplates in the resonator, one at the bottom and the other at the top. The lower mesh is located right above the burner nozzle so that the low-swirl flame is able to freely propagate inside the cylinder cavity geometry whereas the upper metal mesh can be tuned to achieve good overlap between the microwave mode pattern and the flame volume. The flow is characterized for operating conditions without microwave irradiation using particle imaging velocimetry (PIV). Microwave absorption is simultaneously monitored with experimental investigations of the flame in terms of exhaust gas temperature, flame chemiluminescence (CL) analysis as well as simultaneous planar laser-induced fluorescence (PLIF) measurements of formaldehyde (CH2 O) and hydroxyl radicals (OH). Results are presented for experiments conducted in two different regimes of microwave power. In the high-energy regime the microwave field is strong enough to cause a breakdown in the flame. The breakdown spark develops into a swirl-stabilized plasma due to the continuous microwave stimulation. In the low-energy regime, which is below plasma formation, the flame becomes larger and more stable and it moves upstream closer to the burner nozzle when microwaves are absorbed by the flame. As a result of a larger flame the exhaust gas temperature, flame CL and OH PLIF signals are increased as microwave energy is absorbed by the flame.